Implementation Strategies using Artificial Intelligence in Customer Relationship Management - Kumar, B. R. Sarath; Ramana, B. V. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
However, the introduction of Artificial Intelligence (AI) has heralded a new era of CRM in which data-driven insights, automation, and personalization are at the center of customer interaction. AI-powered CRM is a synthesis of cutting-edge technology and classic customer management approaches. It uses machine learning, natural language processing (NLP), and predictive analytics to better understand client behavior, anticipate their requirements, and improve their experiences. Organizations can adapt their services, improve marketing efforts, and provide seamless support by using the power of AI, all while revealing untapped possibilities in their consumer data. This article delves into AI-driven CRM deployment tactics, uncovering the approaches, problems, and rewards of this disruptive approach.